Modelling techniques for rectangular dielectric waveguides - ribs waveguides - Mohd. Supa'at, Abu Sahmah; Mohammad, Abu Bakar; Mohd. Kassim, Norazan (Penerbit UTM Press, 2002)
Rectangular dielectric waveguides have been known as a basic device structure in integrated optics. Result of waveguide analysis is very useful in the study of mode propagation characteristics in a waveguide. In this paper optical propagation in dielectric waveguides have been analyzed using the semi analytical effective index method and a numerical method based on finite difference approach. Full waveguide cross-section and open boundary condition have been considered. This models the exponential decay field at a sufficient distance. Both the propagation characteristic and the field of the guided modes can be calculated very efficiently on a personal computer with modest computational time. This method is applied to the well established test structured for a ribs waveguides. Comparison has been made and some limitations to accuracy have been identified.